AB1414-HPR PATIENTS' EXPERIENCES OF FATIGUE IN AXIAL-SPONDYLOARTHRITIS. (June 2019) - Mercieca, Cecilia; Ryan, Sarah; Borg, Andrew
Abstract : Background: Axial spondyloarthritis (ax-SpA) is a chronic inflammatory arthritis that predominantly affects the spine and the sacroiliac joints. Fatigue is recognised as a central ax-SpA symptom. Ax-SpA fatigue is under-explored and often not addressed. Attention in clinical practice seems to be focused on pain and disease activity. Objectives: The objectives of this study were to explore the meaning, contributing factors and the impact of fatigue on the ax-SpA patients. Self-management and the role of clinicians were also explored. Methods: A qualitative phenomenological approach was used. A purposive sample of 10 patients with ax-SpA, who were experiencing fatigue (and attending a specialist rheumatology clinic were selected. The participants completed a demographic questionnaire, the Bath ankylosing spondylitis disease activity index (BASDAI) and the Bath ankylosing spondylitis functional index (BASFI) outcome measures. Semi-structured interviews using open-ended questions lasted 30-60 minutes. Interviews were tape-recorded and transcribed verbatim. Data was analysed using Colaizzis framework. Two independent reviewers and 5 participants reviewed the data. Results: Five males and five females were selected to participate in the study. The mean age was 46.6 years (29 - 69). Seven participants were working. The mean BASDAI was 5.4 and mean BASFI was 5. Most of the participants had disease duration of longer than 5 years. The six themes that emerged from the data are: The meaning of fatigue Fatigue patterns Factors that modulate fatigue The impact of fatigue Self–management of fatigue Professional support. Fatigue was defined as an unpredictable, extreme and persistent tiredness. Fatigue had a cognitive and physical component, which was not related to physical activity and did not resolve by rest or sleep. Fatigue was distinguished from tiredness. Tiredness was perceived as a normal feeling which occurred after physical activity and was resolved by rest or sleep. The severity, duration and frequency of fatigue varied. Fatigue was described as having a multi-factorial aetiology. Fatigue had an overall negative impact upon participants lives affecting their quality of life, leading to psychological and emotional consequences. Participants struggled to self-manage fatigue, receiving no support from health care professionals. Conclusion: This research has contributed to a better understanding of the patients experiences of ax-SpA fatigue. Fatigue was described as a huge burden and life-changing. Ax-SpA fatigue should be acknowledged in clinical practice. Ax-SpA patients should be asked about fatigue during their clinical consultation. Fatigue should be addressed in its own right and independently from pain and disease activity. Disclosure of Interests: None declared